Trigonuropoda (Baloghiatrigon) dominicana sp. nov. from the Dominican Republic, with notes on the subgenus Baloghiatrigon Hirschmann, 1979 (Acari: Uropodina: Trigonuropodidae) - Kontschán, Jenõ (Zootaxa, 2008)
A new species Trigonuropoda (Baloghiatrigon) dominicana sp. nov. (Acari: Trigonuropodidae) is described from the Dominican Republic. Diagnoses and identification key to all known species of the subgenus Trigonuropoda (Baloghi- atrigon) are given.